r-RAPFISH analysis of fisheries and its management in Mettur (Stanley) Reservoir, India - C. Lloyd Chrispin; P.S. Ananthan (Journal of Indian Fisheries Association, 2023)
Mettur reservoir, located in Salem district, Tamil Nadu, is the largest dam in the state with an average Water Spread Area of 9324 hectares. The reservoir has been a vital resource for fisheries, supporting the livelihoods of local communities. However, the impact of illegal fishing and poaching has led to a significant decline in the fish catch per unit of the reservoir from an average of 1177 kg/ha/year (1961) to an average of 157 kg/ha/year (2015), raising concerns about its sustainability. Understanding the overall sustainability will help in identifying the dimension in which the fishery has to be strengthened through necessary interventions. To address these concerns and gain a comprehensive understanding of the fisheries and their management, a detailed analysis was conducted using both primary and secondary sources of data. The study focused on the five dimensions essential for sustainable fisheries management: Ecology, Economic, Social, Technology, and Governance. However, r-RAPFISH analysis revealed that the overall sustainability of Mettur reservoir fisheries is in “Quite” status (Sustainability score – 74.51%), which is obtained by taking an average of sustainability value obtained by the reservoir in each of the five dimensions [Ecology - 83.86%; Economic-90.40%; Social - 44.93%; Technology - 85.59%; Governance -67.76%]. It has also been observed that the social and governance aspects of the fisheries management in Mettur reservoir have to be improved to get an overall ‘good’ sustainable development status.